Penataan Manajemen Operasional Pengelolaan Air Bersih pada BUMDES - Esra Tarigan; Parinton Banjarnahor (Mahesa Research Center, 2022)
BUMDes is a village business institution that is managed by the community and village government in an effort to strengthen the village economy and is formed based on the needs and potential of the village. BUMDes is a pillar of economic activity in the village that functions as a social and commercial institution. In addition, BUMDes also acts as a social institution that favors the interests of the community through its contribution to the provision of social services and commercial institutions that aim to seek profit through their contribution to the provision of social services. This study aims to describe the village drinking water management model and the problems it faces. The research was conducted in the area of Kacaribu Village, Kabanjahe District, Tanah Karo. The problem studied is how the management is viewed from the institutional aspect, water availability, number of users, clean water needs, guidelines governing and financial management. This type of research is a survey with a qualitative and quantitative descriptive approach. The subject of research is the head of the family. The availability of water is very sufficient but customer needs have not been fully met. If the Kacaribu BUMDes can operate effectively and efficiently, the Kacaribu village community will not lack clean water because in one month there is still 13,445 m3, which is equivalent to meeting the needs of clean water on average 259 people/month.